2012
DOI: 10.1002/jbt.21423
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal inhibition of cytosolic ascorbate peroxidase from Nicotiana tabacum

Abstract: Methylglyoxal (MG) is one of the aldehydes accumulated in plants under environmental stress. Cytosolic ascorbate peroxidase (cAPX) plays a key role in the protection of cells from oxidative damage by scavenging reactive oxygen species in higher plants. A cDNA encoding cAPX, named NtcAPX, was isolated from Nicotiana tabacum. We characterized recombinant NtcAPX (rNtcAPX) as a fusion protein with glutathione S‐transferase to investigate the effects of MG on APX. NtcAPX consists of 250 amino acids and has a deduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Addition of cysteine or methionine counteracted the detrimental effects of MG at 0.1 μM concentrations and less, thereby implicating the involvement of sulfhydryl groups of key enzymes (Mankikar and Rangekar 1974 ). Other growth processes, apart from seed germination, such as root elongation and chlorosis are also affected by MG (Hoque et al 2012a ). Hoque and coworkers have shown that 0.1 mM MG delays root elongation in Arabidopsis , whereas a weeklong exposure to 1 mM MG inhibited germination by 21 % and also repressed root elongation along with inducing chlorosis.…”
Section: How Methylglyoxal Brings About Toxicity In Cells?mentioning
confidence: 97%
See 1 more Smart Citation
“…Addition of cysteine or methionine counteracted the detrimental effects of MG at 0.1 μM concentrations and less, thereby implicating the involvement of sulfhydryl groups of key enzymes (Mankikar and Rangekar 1974 ). Other growth processes, apart from seed germination, such as root elongation and chlorosis are also affected by MG (Hoque et al 2012a ). Hoque and coworkers have shown that 0.1 mM MG delays root elongation in Arabidopsis , whereas a weeklong exposure to 1 mM MG inhibited germination by 21 % and also repressed root elongation along with inducing chlorosis.…”
Section: How Methylglyoxal Brings About Toxicity In Cells?mentioning
confidence: 97%
“…The stress-responsive gene expression in Arabidopsis has been investigated using an ABA-defi cient mutant, aba2-2 in response to MG (Hoque et al 2012a ). For this purpose, the transcription of ABA-independent gene, RD29A -and ABAdependent genes, RD29B and RAB18, was monitored in the presence and absence of MG in 2-week-old Arabidopsis wild type and aba2 -2 mutant seedlings.…”
Section: Methylglyoxal As a Signaling Molecule In Biological Systemsmentioning
confidence: 99%
“…It was also found that OsDMI3 functions upstream to OsMPK1 in regulating the activities of antioxidant enzymes and the production of H 2 O 2 in rice (Shi et al 2012(Shi et al , 2014. In maize, ZmCCaMK was identifi ed to be essential for ABAinduced antioxidant defense ( Ma et al 2012a ). However, still there are not many reports on the role of CCaMK in abiotic stress; hence, in this article, I shall restrict the discussion to CDPK and CBL-CIPK proteins for their involvement in abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…MG levels have been reported to elevate during various abiotic stress conditions and are responsible, to some extent, for the damage that occurs to cellular machinery under stress (Yadav et al 2005a ;Hoque et al 2012a ). The toxicity of MG is believed to be due to its ability to interact with and modify protein and nucleotide moieties leading to loss of cell viability culminating in cell death (Thornalley 1998(Thornalley , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rubisco, the 33-kD oxygen-evolving complex, and the light-harvesting complex are modified by malondialdehyde under heat stress conditions in vivo (Yamauchi et al, 2008;Yamauchi and Sugimoto, 2010). Furthermore, recent studies have revealed that lipidderived RCS modify not only chloroplastic enzymes but also cytosolic and mitochondrial enzymes in plant leaves (Fujita and Hossain, 2003;Hoque et al, 2012;Mano et al, 2014b). These facts indicate that the production and the accumulation of lipid-derived RCS should be dangerous for plants.…”
mentioning
confidence: 99%